Wajah Sang Calon Presiden: Prabowo Subianto Lewat Analisis Isi Instagram (Faculty of Communications Science, Dr. Soetomo University, 2022)
- Indonesia will hold presidential elections in 2024. Several presidential candidates have begun to be voiced by political parties. One of them is Prabowo Subianto who currently serves as the Minister of Defense of the Republic of Indonesia. Prabowo Subianto himself has fought four times in a row in the presidential election, and 2024 is the fifth time in this political contest. Since the development of the internet, social media has become a channel for conveying messages. One that is growing rapidly and is used by public leaders is Instagram. Therefore it is important to see what public leaders, in this case Prabowo Subianto, want to convey to the public through the official Instagram account. The face or image of a public leader can be seen clearly through uploads made on Instagram. This research uses content analysis, and uses data from October 23, 2019 to December 1, 2022. This time span is since Prabowo Subianto was appointed as the Minister of Defense of the Republic of Indonesia. Through content analysis it was found that Prabowo communicated himself as a competent leader in his field. He also displays a fairly balanced professional side and personal life. Prabowo also described his close relationship with politicians and government agents as well as non-political public figures. It was found that the uploaded content lacked closeness with the community or the people. While the presidential election is very dependent on the people's vote at the time of the election. Instagram as a social media platform can be used to display images or messages for its audience.